Social Media Use and Serious Psychological Distress Among Adolescents - Riti Shimkhada; Ninez A Ponce (JMIR Publications, 2024)
AbstractThis Research Letter describes the increasing trend of almost-constant social media use among California adolescents and the association with serious psychological distress, focusing on the influence of familial and experiential factors.